The new classification of periodontal and perimplant conditions and diseases from an evolutionary perspective - Carla María García San Juan; Rubén Darío García Núñez; Maria Aurelia San Juan Bosch (Medisur)
In Periodontology it is very important to establish classification criteria, which allow understanding, comparing, ordering and ranking periodontal diseases. These classification criteria are based on available scientific evidence, but not immutable. The objective of this review is to describe the evolution of the classifications of periodontal conditions, emphasizing the main changes and characteristics of the most recent of these. For this, an updated review of the bibliography was carried out. The articles were identified through the automated search in the SCOPUS and GOOGLE reference systems databases. 16 original articles were selected. It is concluded that multiple and diverse classification systems for periodontal conditions have been proposed over the years, among them the following stand out: Weski (1921); WHO (1961), adopted and modified by Cuba, later; Prichard (1972); American Academy of Periodontology (1989 and 1999), until the most recent one established in 2017 at the World Classification Workshop. The most prominent aspects of this new classification are the re-categorization of periodontitis, a section for periodontal health, as well as another for peri-implant diseases and conditions.